The Response from the Greater Mekong subregion to China’s Belt and Road Initiative (BRI) : crossing the Mekong River by Feeling the Stones - Nisit Panthamit (Faculty of Economics Chiang Mai University, 2023)
Greater Mekong Sub-region (GMS) is a subregional economic cooperation, which was designed to enhance economic relations among the six countries of the Greater Mekong region, including Cambodia, China (Yunnan and Guangxi Zhuang Autonomous Region), Lao PDR, Myanmar, Thailand and Viet Nam. The program of cooperation started in 1992 with the support from the Asian Development Bank. Priority sectors of the GMS program are transportation, energy, telecommunications, environment, human resource development, tourism, trade private sector investment and agriculture. GMS is part of the ASEAN countries, China is the south, although the economy is relatively backward, closely related with China in politics, economy, and culture. Moreover, in the ten ASEAN countries, China and the five countries is the closest, with convenient geographical advantages, unique and important position. China and GMS region can represent the inland relationship between China-ASEAN countries from the upper part of ASEAN. As a result, China has become more and more influential in the GMS countries as measured by its trade value and investment stock in the region. In addition, the path of economic spill-over effects leading to regional stability and prosperity is also China’s incentive. From the geographical point of view, China and CLMVT countries, their land is adjacent, the Mekong River flows through China, Laos, Myanmar, Thailand, Cambodia and Vietnam. The Mekong River Basin development has become an important area of cooperation between China and neighboring country for several decades. The main point of this book mainly to investigate, the role of Chinese’ investment under BRI since has been criticized by the international community whether China’s OFDI under BRI has the potential to reshape regional and international geopolitics. The BRI has been presented, theorized, investigated and parsed across disciplines, methods and perspectives. Description and knowledge are coupled with a lack of program definition that encourages hope and speculation. Measured analysis is essential for lack of program definition that encourages hope and speculation. Measured analysis is essential for understanding what the Belt and Road Initiative means for the host countries and partner nations it is understanding what the Belt and Road Initiative means for the host countries and partner nations passes through and engages. However, from the best of our knowledge, the book is lacking in connection with the dimensions that China has invested outside in terms of the physical impact of China s mega-projects in the Mekong region, CLMVT. Given this, this book aims to answer these questions, this main content of this book is presented into ten chapters. By drawing the relationship between China with GMS’s five countries and 2) provide the framework of to characterize the China’s role and its impacts for the ambiguity regarding the nature and impacts of established of China ‘role under Belt and Road Initiative (BRI) in CLMVT. The key elements behind China’s role in these five countries incorporate into the broader Asian sphere with a climate and BRI comparison of similar research in other region.